Plummer-Vinson Syndrome: A Case Report - Gedam, DS; Mandliya, J; Verma, M (Journal of Nepal Paediatric Society, 2011)
Plummer-Vinson also known as sideropenic dysphagia is a disease that is characterized by classical triad of iron deficiency anemia, dysphagia and esophageal web. It is known to mostly affect white female mainly, but cases have been reported from other ethnic group in the literature. Treatment is very promising especially when it is not associated with carcinoma. DOI: http://dx.doi.org/10.3126/jnps.v31i3.4259 J Nep Paedtr Soc 2011;31(3): 254-256